Duties And Importance of the Pedagogical Council in Preschool Educational Organizations - Malikova Sanobar Anarbayevna (Genius Publishing Group, 2023)
The article discusses the organization of pedagogical councils in preschool educational organizations, their structure, tasks performed by pedagogical councils, their importance. , can be used by free and independent researchers.
Keywords: pedagogical council; collegial management; encouragement